Measuring knowledge and attitudes towards the utilization of pharmacogenetic testing among physicians. Issue 2 (7th March 2019) - Muflih, Suhaib; Bleidt, Barry A.; Lafferty, Lynn; Shawaqfeh, Mohammad S.; Alvarez, Goar
Abstract: Objective: Pharmacogenetic (PGx) testing is a relatively new available diagnostic tool, which aims to prescribe tailored medications based on genetic differences. However, this innovation has been slowly adopted by physicians. This study aims to test Rogers's diffusion of innovation theory to assess knowledge and attitudes towards the use of PGx testing among physicians. Method: A sample of community physicians in South Florida was invited to complete an online survey about PGx testing. Practicing physicians who willing to sign the participation letter were included. The survey collected data on sociodemographics, knowledge of and attitudes towards PGx testing. Multiple dimensions of knowledge (i.e. prior experience) and attitude (i.e. relative advantage) were measured. Key findings: One hundred and fourty‐eight physicians participated in this study. Physicians' actual PGx knowledge scores were averaged and significantly predicted by gender ( P  < 0.01), area of practice ( P  < 0.01) and prior experience ( P  < 0.05). The majority of physicians expressed optimistic attitudes towards PGx testing. Attitude scores were significantly predicted by gender ( P  < 0.05), the relative advantage ( P  < 0.05) and compatibility ( P  < 0.01) of testing. Barriers to PGx testing adoption including lack of insurance support, uncertainty about the clinical utility and unavailability of PGx testing at workplace were reported. Conclusions: Knowledge of PGx testing among physicians was moderate despite the expressed needs and favourable attitudes. Collaborative efforts to address the potential inhibitors may foster the integration of PGx testing into clinical practice. The need for additional courses and training in the field of pharmacogenetics is warranted.